2019
DOI: 10.1080/15476286.2018.1558907
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional dynamics of microRNAs and their targets during Drosophila neurogenesis

Abstract: During Drosophila melanogaster embryogenesis, tight regulation of gene expression in time and space is required for the orderly emergence of specific cell types. While the general importance of microRNAs in regulating eukaryotic gene expression has been well-established, their role in early neurogenesis remains to be addressed. In this survey, we investigate the transcriptional dynamics of microRNAs and their target transcripts during neurogenesis of Drosophila melanogaster. To this end, we use the recently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…miRNAs are critical to the post-transcriptional regulation of gene expression through sequence complementarity. In pace with the development of next-generation sequencing (NGS), genome-wide identification of miRNAs, increasingly, have been reported in plants (Yu et Menzel et al 2019). In poultry, egg-laying performance is commercially important and determined by ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are critical to the post-transcriptional regulation of gene expression through sequence complementarity. In pace with the development of next-generation sequencing (NGS), genome-wide identification of miRNAs, increasingly, have been reported in plants (Yu et Menzel et al 2019). In poultry, egg-laying performance is commercially important and determined by ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to regulate neurogenesis by repressing yan, which is a transcription factor that inhibits neuronal differentiation (Flynt et al, 2010). Menzel et al, 2019 also reported that miR-1017 levels were downregulated in the neuroblasts when they analyzed miRNA dynamics during neurogenesis in Drosophila (Menzel et al, 2019). Another mirtron, hsa-miR-877 was shown to target FXR2 gene (Fragile X mental retardation syndrome-related protein 2) in neuronal SH-SY5Y cells (Sibley et al, 2012).…”
Section: Emerging Roles Of Mirtrons In Regulating Cellular Processesmentioning
confidence: 99%
“…MiRNAs are short noncoding RNAs containing 21-22 nucleotides participating in wide range of biological mechanisms. A high number of miRNAs have been detected in eukaryotic cells (Menzel, McCorkindale, Stefanov, Zinzen, & Meyer, 2019). MiRNAs can thoroughly bind to mRNA after transcription.…”
Section: Mirnas Function At a Glancementioning
confidence: 99%